Implementing Brief Tobacco Cessation Interventions in Community Pharmacies: An Application of Rogers' Diffusion of Innovations Theory - Katy Ellis Hilts; Robin L. Corelli; Alexander V. Prokhorov; Susan M. Zbikowski; Alan J. Zillich; Karen Suchanek Hudmon (MDPI AG, 2022)
Pharmacists, as highly accessible members of the healthcare team, have considerable potential to address tobacco use among patients. However, while published data suggest that pharmacists are effective in helping patients quit, barriers exist to routine implementation of cessation services in community pharmacy settings. Within the context of a randomized trial (n = 64 pharmacies), surveys were administered over a period of 6 months to assess pharmacists' perceptions of factors associated with the implementation of "Ask-Advise-Refer", a brief intervention approach that facilitates patient referrals to the tobacco quitline. Study measures, grounded in Rogers' Diffusion of Innovations Theory, assessed pharmacists' perceptions of implementation facilitators and barriers, perceptions of intervention materials provided, and perceived efforts and personal success in implementing Ask-Advise-Refer at 6-months follow-up. Findings indicate that while the brief intervention approach was not difficult to understand or implement, integration into normal workflows presents greater challenges and is associated with overall confidence and implementation success. Lack of time was the most significant barrier to routine implementation. Most (90.6%) believed that community pharmacies should be active in promoting tobacco quitlines. Study results can inform future development of systems-based approaches that lead to broad-scale adoption of brief interventions, including but not limited to tobacco cessation, in pharmacy settings.